Assessment of psychomotor domain in hydraulics laboratory / Noor Raifana Ab Rahim, Nur Zaidani Wati Mohd Darwis and Juwita Asfar - Ab Rahim, Noor Raifana; Mohd Darwis, Nur Zaidani Wati; Asfar, Juwita (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Graduate students, particularly in engineering courses, are required to have high knowledge in engineering and technical skills. As the technology evolving rapidly, Institutions of Higher Learning should produce qualified graduates to fulfil demand in the engineering industries upon receiving accreditation from the Engineering Technician Education Programme Accreditation Standard (ETAC). A good programme should have proper Programme Outcomes, developed based on three domains from Bloom's Taxonomy that comprised of cognitive, psychomotor and affective. The overall goal of engineering education is to prepare students to practice engineering. Psychomotor domains help students to improve their technical skill. To improve student's technical skills, engineering laboratory courses allow students to apply engineering knowledge and conduct experiment on their own. Their skills will be assessed based on methodology and rubrics. The assessment rubric is a combination of four aspect domains consist of perception, set, guided response and mechanism. The analysis consists of categorizing the students in terms of their performance by comparing between two assessments, Practical Test 1 and 2. The marks obtained by students were evaluated based on four categories; poor, weak, average and good.